Penerapan Senam Rematik Terhadap Intensitas Nyeri Rematik Pada Lansia Di Wilayah Kerja Puskesmas Sambi - Lusi Kusnul Cotimah; Exda Hanung Lidiana (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: One of the diseases that often attacks the joints in the elderly is Rheumatoid Arthritis (RA). The prevalence of Rheumatoid Arthritis (RA) in Central Java in 2018 was 6.78% of the total population in Central Java. If not treated immediately, this disease can cause pain, limited physical mobility, and even disability and paralysis. One of the non-pharmacological therapies to reduce pain that is easy to do for elderly people with arthritis is rheumatic gymnastics. Rheumatic gymnastics is a series of physical exercises to stretch muscles and make joints flexible. Objective: To figure out the results of the application of Rheumatic Gymnastics on the intensity of rheumatic pain in the elderly. Method: This type of application is descriptive in the form of a case study. Rheumatism exercises were given to the elderly who experienced Rheumatoid Arthritis (RA) pain. This application was carried out for 4 weeks with a frequency of one time a week for 8 minutes. Results: There was a decrease in the pain intensity scale for the two respondents by 4 scales, from the moderate pain category to the mild pain category. Conclusion: Rheumatic gymnastics can reduce the pain intensity scale in elderly people with arthritis.